Human resource management strategy and practice - Nankervis, Alan; Baird, Marian; Coffey, Jane; Shields, John (Cengage Learning Australia, 2023)
Human Resource Management: Strategy and Practice provides you with key concepts and practical information that you will use in your study of human resource management. A range of contemporary regional and international examples are included alongside detailed coverage on the future of work and emerging issues in human resource management. This is the only resource that uses the Australian HR Institute (AHRI) Model of Excellence to teach the required behaviours and capabilities required by an HR practitioner.